Semicircular Canal Fibrosis as a Biomarker for Lateral Semicircular Canal Function Loss - Van Rompaey, Vincent; De Belder, Frank; Parizel, Paul; Van de Heyning, Paul (Frontiers in Neurology, 2016)
Background and purpose Radiological abnormalities at the level of the semicircular canals are frequently observed without known correlation to a pathologic condition or function. They include narrowing or sclerosis on computed tomography (CT) and narrowing or signal loss on T2-weighted magnetic resonance imaging (MRI). Our hypothesis was that these radiological abnormalities at the level of the semicircular canals reflect an aspecific but advanced stage of vestibular decay. Materials and methods Retrospective study in 35 consecutive patients with bilateral profound deafness eligible for cochlear implantation. Electronystagmography, CT, and MRI were performed as part of evaluation for cochlear implant candidacy. Results In our population, 31.4% had a bilateral lateral semicircular canal function loss, while 11.4% had a unilateral lateral semicircular canal function loss. CT-scan abnormalities did not correlate to lateral semicircular canal function loss at a statistically significant level. However, abnormalities observed on MRI correlated significantly with ipsilateral lateral semicircular canal function loss. This statistically significant difference was present not only if abnormalities were observed in at least one of the semicircular canals but also if we studied the posterior, superior, and lateral semicircular canals separately. Conclusion Semicircular canal abnormalities on T2-weighted MRI (including narrowing and/or signal loss in one or more semicircular canals) are correlated to lateral semicircular canal function loss.